Accuracy of extended point-of-care lung ultrasound (EPLUS) for aetiological differentiation of lower respiratory tract infections: a prospective cohort study from India - Ruby, Lisa C.; Weber, Stefan F.; Kadavigere, Rajagopal; Acharya, Raviraj Vedavyasa; Magazine, Rahul; Shastry, Barkur Ananthakrishna; Joylin, Sowmya; Sultanli, Ayten; Heller, Tom; Saravu, Kavitha; Bélard, Sabine (Infectious diseases, 2025)
Infectious respiratory diseases significantly cause morbidity and mortality worldwide, particularly in low- and middle-income countries (LMICs) with limited diagnostic resources. This study explored the utility of lung ultrasound (LUS) paired with extra-pulmonary point-of-care ultrasound (POCUS) for differentiating infectious aetiologies in lower respiratory tract infections (LRTI). This prospective cohort study was conducted at a tertiary care centre in India. We recruited consenting adults with suspected LRTI who underwent extended point-of-care lung ultrasound (EPLUS). The protocol included thoracic and abdominal views assessing for lung consolidations and B-lines, pleural effusion, pericardial effusion, focal splenic lesions, and abdominal lymphadenopathy and correlated these with patients’ final diagnoses. We included 322 participants in our analysis cohort, which had a notable prevalence of previously existing chronic lung conditions (21%) and an HIV-prevalence of 5%. Infectious lung disease was identified in 48% of patients, comprising 35% with non-TB LRTI and 13% with TB. Non-infectious lung disease was present in 21% of patients. LUS detected consolidations in 75% and >3 B-lines in 72% of participants. LUS findings were mostly non-specific and prevalent across both infectious and non-infectious conditions. Extra-pulmonary ultrasound findings, such as pericardial effusion and splenic lesions, findings common in disseminated tuberculosis, were rare. The study highlights the high sensitivity of LUS for detecting pulmonary changes but revealed low specificity to differentiate pulmonary conditions, especially in the presence of pre-existing comorbidities. Future research should explore the accuracy of combinations of clinical characteristics and ultrasound findings in algorithmic approaches, which may improve diagnostics in resource-limited settings.